2019
DOI: 10.1038/s41419-019-1763-2
|View full text |Cite
|
Sign up to set email alerts
|

Increase in HDAC9 suppresses myoblast differentiation via epigenetic regulation of autophagy in hypoxia

Abstract: Extremely reduced oxygen (O 2 ) levels are detrimental to myogenic differentiation and multinucleated myotube formation, and chronic exposure to high-altitude hypoxia has been reported to be an important factor in skeletal muscle atrophy. However, how chronic hypoxia causes muscle dysfunction remains unknown. In the present study, we found that severe hypoxia (1% O 2 ) significantly inhibited the function of C2C12 cells (from a myoblast cell line). Importantly, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…Recently, the HDAC8-selective inhibitor HMC was shown to induce autophagy in MCF-7 cells 42 . In response to hypoxia in a myoblast cell line, class IIa HDAC9 was significantly increased, thereby inhibiting intracellular autophagy through direct binding to the promoter regions of Beclin 1, ATG7 and LC3 43 .…”
Section: Kats and Kdacs And Autophagy Regulationmentioning
confidence: 99%
“…Recently, the HDAC8-selective inhibitor HMC was shown to induce autophagy in MCF-7 cells 42 . In response to hypoxia in a myoblast cell line, class IIa HDAC9 was significantly increased, thereby inhibiting intracellular autophagy through direct binding to the promoter regions of Beclin 1, ATG7 and LC3 43 .…”
Section: Kats and Kdacs And Autophagy Regulationmentioning
confidence: 99%
“…It also suggests that the level of O2 may determine the final role of hypoxic environment. Epigenetic events are essential to establish and maintain the distinct cell lineages and have been shown to be crucial players controlling the fate and function of MSCs and MuSCs(Nakade et al, 2017 ; Zhang et al, 2019 ). More recently, a study showed MuSCs forced to express Msx1 exhibited increased proliferation index as well as promoted SSEA1 and Pax7 expression, but restricted MyoD expression and accessed osteogenic genes (Ding et al, 2017 ).…”
Section: Hypoxia and Its Role In Diseasementioning
confidence: 99%
“…Hdac9 can repress the transcription of some autophagy genes by the direct binding of the relative promoters. The authors propose that through this mechanism Hdac9 regulates autophagy and muscle differentiation in hypoxic conditions [ 86 ]. In the context of cancer progression, this environmental control on HDAC9 levels could provide an important contribution to the adaptation of the cancer cells to a hostile hypoxic environment.…”
Section: Regulation Of Hdac9 Expression and Cancermentioning
confidence: 99%